The Effect of Ball Feeling Variation Training on Dribbling Skills In Futsal Extracurricular Members of Senior High School 1 Jalancagak - Mohammad Sya’ban Fadhillah; Abdul Salam Hidayat; Abdulloh Abdulloh (UNIVERSITAS NEGERI MAKASSAR, 2022)
This study aims to determine the effect of ball feeling variations on dribbling skills in futsal extracurricular members of SMA Negeri 1 Jalancagak. This study uses a quantitative approach. When viewed from the type of data presented, this type of research is an experiment with a